Bilingualism and Cognitive Reserve: Empirical Inconsistencies and New Methodological Proposals [el Bilingüismo Como Protección Ante la Demencia: Inconsistencias Empíricas y Nuevas Propuestas Metodológicas] - Contreras-Torregrosa, M; Muñoz-Arias, E (Universidad Complutense de Madrid, 2016)
Bilingualism and cognitive reserve: Empirical inconsistencies and new methodological proposals. Cognitive decline throughout healthy or pathological aging can be slowed down by experiences which foster cognitive reserve. In this sense, some studies have suggested that bilingualism may delay the onset of Alzheimer's disease. However, the evidence stems from retrospective approaches yielding contradictory results. The present paper addresses these findings, identifies possible lurking variables, and outlines methodological alternatives thereof. First, we characterize possible confounding factors, namely: The criteria to establish bilingualism, differences in sample design, the instruments used to examine cognitive skills, and variables known to modulate life-long cognition. Second, we propose that these limitations could be largely circumvented through experimental approaches and the use of adequate instruments to measure such variables. Moreover, future research should incorporate tasks yielding predictable patterns of contrastive performance between bilinguals and monolinguals (bilingual disadvantages in vocabulary, null effects in working memory, advantages in inhibitory control and other executive functions), and other which could offer valuable insights (e. g., proactive interference tasks). Such considerations may shed light not just on the relationship between bilingualism and cognitive reserve, but also on more general mechanisms of cognitive compensation. ©2016 Noelia Calvo, Laura Manoiloff, Edinson Muñoz, Marcela Contreras, Agustín Ibáñez y Adolfo M. García.